Design and Synthesis of Chitosan—Gelatin Hybrid Hydrogels for 3D Printable in vitro Models - Magli, Sofia; Rossi, Giulia Beatrice; Risi, Giulia; Bertini, Sabrina; Cosentino, Cesare; Crippa, Luca; Ballarini, Elisa; Cavaletti, Guido; Piazza, Laura; Masseroni, Elisa; Nicotra, Francesco; Russo, Laura (Frontiers in Chemistry, 2020)
The development of 3D printable hydrogels, based on the crosslinking between chitosan and gelatin, is proposed. Chitosan and gelatin have been both functionalized with methyl furan groups. Chemical modification was performed by reductive amination with methyl furfural involving the lysine residues of gelatin and the amino groups of chitosan, to generate the hydrogels with tailored properties. The methyl furan residues present in both polymers have been exploited for the efficient crosslinking via a Diels-Alder ligation with PEG-Star-maleimide in cell compatible conditions. The obtained chitosan and gelatin based biopolymers has been employed to formulate hydrogels and 3D printable hydrogel patterns and used to investigate the preliminary processability and biocompatibility.